Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1002/(sici)1097-4547(19990715)57:2<185::aid-jnr4>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of GABAA receptor β1, β2/3, and γ2 immunoreactivity in the rat retina

Abstract: GABA (gamma-aminobutyric acid) is the major inhibitory neurotransmitter in the mammalian central nervous system and plays an important role in neuronal physiology during ontogenesis. The distribution of the beta1-, beta2/3-, and gamma2-subunit of the GABAA receptor in the rat retina was studied during postnatal development using immunohistochemical methods. All subunits were found at birth. However, each subunit showed a unique staining pattern with a different local distribution. The immunoreactivity pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
4
7
0
Order By: Relevance
“…This temporal profile in the generation of amacrine synapses matches that previously suggested by following changes in total inhibitory synapse density across the mouse IPL [29]. Rapid amacrine synaptogenesis during the first and second postnatal weeks also appears to occur in other species, as revealed by immunostaining for GABA A receptors, glycine receptor subunits or gephyrin on RGCs, for example in rat and rabbit retina [37,56]. …”
Section: Discussionsupporting
confidence: 81%
“…This temporal profile in the generation of amacrine synapses matches that previously suggested by following changes in total inhibitory synapse density across the mouse IPL [29]. Rapid amacrine synaptogenesis during the first and second postnatal weeks also appears to occur in other species, as revealed by immunostaining for GABA A receptors, glycine receptor subunits or gephyrin on RGCs, for example in rat and rabbit retina [37,56]. …”
Section: Discussionsupporting
confidence: 81%
“…[ 3 Η]Flunitrazepam binding showed a significant decrease by 25% between P17 and P60 in IPL of normal rat retina. Previous studies have shown that the typical adult layering of GABA A receptor subunit immunoreactivity into distinct bands in the IPL appeared by the 3rd postnatal week [25,37]. Our results could imply that GABA A /benzodiazepine receptors are decreasing even after the adult stratification pattern in IPL has been reached.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, almost all GABA A receptor subunits were expressed in the IPL, while in the OPL a several-fold lower staining intensity for α1, α2, β2/3 and γ2 subunits has been reported [20,25]. A selective synaptic distribution of GluR6/7 and KA2 kainate receptor subunits has been indicated in both plexiform layers of rat retina, being more prominent in the IPL [8,33].…”
Section: Discussionmentioning
confidence: 92%
“…Several lines of evidence suggest that these effects are mediated by ambient GABA released paracrinally from maturing neurons or from glial cells (Matsutani and Yamamoto, 1998). In the neonatal rat retina, for example, diffuse subunit staining (characteristic of extrasynaptic receptors) for various GABA A receptor subunits precedes the punctate staining pattern (characteristic of synaptic receptors) by a couple of days (Koulen, 1999). …”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%